Pattern of Finger Prints in The Population of Rawalpindi - Rizwana Qayyum, Abdul Mateen, Sajid Hameed, (Journal of Rawalpindi Medical College, 2013)
Background: To study the pattern of finger prints in the population of Rawalpindi. Methods: In this cross sectional study a data tool was designed and a group of fifty medical students of third year MBBS class of Rawalpindi Medical College were trained to collect the relevant data from the study population. The data comprised of socio-demographic details and collection of full hand print with the help of ink pad from the study population. A sample of n=500 subjects (females n=222 and males n=278) were included in the study using convenient sampling method. The criteria of inclusion was the age of the respondents i.e. ages from 20 years onwards were sampled. Results: The majority of the respondents (n=283) were found to have Loop type of finger print followed by whorl (n=130), composite (n=45) and Arch type of print (n=42). The cross tabulation of variables Gender and Type of finger print showed the association to be of less statistical significance as the p- value found was much greater than 0.05. Conclusion: There lies a statistical variation in the occurrence of finger print pattern in our country as compared to the existing data available for the whole world. There is no significant association of finger print type and gender